2021
DOI: 10.1159/000512526
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Diversity of Cerebral Sinovenous Thrombosis and Arterial Ischaemic Stroke in the Neonate: A Surveillance Study

Abstract: <b><i>Introduction:</i></b> Relative risk, risk factors, clinical presentation, onset of symptoms, and age at diagnosis differ between arterial ischaemic stroke (AIS) and cerebral sinovenous thrombosis (CSVT) in neonates. Distinguishing these 2 entities in time clinically can be of eminent importance. <b><i>Methods:</i></b> Active surveillance for AIS and CSVT was performed in 345 German paediatric hospitals. Only cases confirmed by cerebral MRI were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…Besides thrombophilia mutations, other maternal and neonatal risk factors have been cited as important contributors to the development of cerebral venous thrombosis. The univariate analysis of a nested case–control study revealed that male sex, preterm birth, hypoxia, and related indicators (umbilical artery pH < 7.1; 5 min Apgar score < 7; intubation/mask ventilation; perinatal asphyxia) were significantly associated with neonatal cerebral sinovenous thrombosis [ 18 ]. The majority of our patients were males, born through vaginal delivery, and had a mean Apgar score at 5 min and SD of 6 ± 2.3 (range: 2–8; 95% CI: 4.19–7.80).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides thrombophilia mutations, other maternal and neonatal risk factors have been cited as important contributors to the development of cerebral venous thrombosis. The univariate analysis of a nested case–control study revealed that male sex, preterm birth, hypoxia, and related indicators (umbilical artery pH < 7.1; 5 min Apgar score < 7; intubation/mask ventilation; perinatal asphyxia) were significantly associated with neonatal cerebral sinovenous thrombosis [ 18 ]. The majority of our patients were males, born through vaginal delivery, and had a mean Apgar score at 5 min and SD of 6 ± 2.3 (range: 2–8; 95% CI: 4.19–7.80).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations in neonates are often subtle and nonspecific, especially at the presentation, and include seizures, lethargy, irritability, poor feeding, or changes in muscle tone [ 17 , 18 ]. The CSVT-associated intracranial hypertension syndrome is a medical emergency, which can lead to brain tissue herniation and death [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Durch den gezielten Einsatz von Schallköpfen mit höherer Frequenz lässt sich die diagnostische Aussagekraft erhöhen [ 24 ]. Die Doppler-cUS erlaubt Aussagen zur intrazerebralen Perfusion und wird zur Diagnostik von arteriellen und venösen Ischämien in der Neonatalperiode eingesetzt [ 72 , 88 ].…”
Section: Zerebraler Ultraschallunclassified
“…In der initialen Diagnostik des neonatalen arteriell-ischämischen Schlaganfalls, der Sinusvenenthrombose [ 88 ], von neonatalen Infektionen und Hirnfehlbildungen ist die MRT nicht mehr wegzudenken. Darüber hinaus ist sie aufgrund der besseren Darstellung von strukturellen Auffälligkeiten ein wertvolles Instrument in der klinischen Routinediagnostik unklarer neurologischer Symptome beim Neonaten, wie z.…”
Section: Magnetresonanztomographieunclassified
See 1 more Smart Citation